A Tuvan manuscript of the Sutra of Eight Luminous as a Booklore Talisman - Mirzaeva , Saglara V. (The New Research of Tuva, 2021)
The article introduces the text of the Mongolian manuscript "Naiman gegen neretü ǰuu tarni" (Talisman-tarni Called Eight Luminous) kept in the National Museum of the Republic of Tuva (M-828). It contains valuable data on the tradition of buu / bu talismans in Buddhism of Tibet and Mongolia.This manuscript, another version of which is found in the collection of Harbukhyn Balgas (Bulgan aimag of Mongolia), includes images of various talismans, followed by sacred spells and brief description of their functions. In total, thirty-three images of talismans were identified in the manuscript. All pursue various goals — from family welfare and prosperity to the highest goal of the Buddhist path.The source manuscript is of a compilative character: the list of the talismans, which, obviously, is ritually intended, is followed by a short narrative telling how this booklore talisman named “The Eight Luminous” was given by Buddha Sakyamuni. Description of some tarni talismans (buu tarni) is given according to the text. The article provides also transliteration of the manuscript.
Keywords: The Sutra of the Eight Luminous; tarni talisman of the Eight Luminous; booklore talisman; buu talisman; Buddhism in Tibet and Mongolia; National Museum of the Republic of Tuva; Tuva